G174(P) A regional snapshot of paediatric epilepsy care. (May 2019) - Shipp, A; Hindley, D; Jameson, H
Abstract : Aims: To delineate the structure of epilepsy services available at secondary care level, with the aim of identifying gaps, unmet needs and inequalities in provision across the region. Methods: Questionnaires were sent to ten paediatric epilepsy services across the region and completed by the local paediatric epilepsy nurse specialists. Categories taken into account included numbers of children being cared for by local teams, and how this translated into epilepsy specialist nursing numbers. Waiting time for a new patient appointment and the availability of epilepsy specialist nurses in clinic along with the availability of teenage and transition clinics within each locality were also considered. Results: There was a big variation in the ratio of patients per epilepsy nurse specialist, ranging from 1:90 up to 1:525. 50% of services had an epilepsy nurse with prescribing qualifications. Reassuringly waiting times were reasonable across the board, on average 4–6 weeks with 8 out of 10 respondents able to see a new case within 2 weeks if required. In 7 out of 8 respondents a child given a diagnosis will have an epilepsy nurse either present or referred. It was disappointing to see that 70% of units did not have a dedicated new patient clinic with and epilepsy nurse in attendance. Results varied in other parameters with only 30% having a dedicated teenage clinic, but 80% can offer transition appointments. Access to clinical psychology was an area of concern across the region with only 20% having easy access and only two units were accessing best practice tariff for epilepsy. Conclusions: It was reassuring to see that there is good access to epilepsy services across the region, but several of the areas addressed by the survey left significant room for improvement, particularly in relation to access of clinical psychology services and access to best practice tariffs. More work is needed both at regional and national level to ensure equality In access to services to improve outcomes for patients in the long term.